2018
DOI: 10.1016/j.vetpar.2018.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Ticks from cats in the United States: Patterns of infestation and infection with pathogens

Abstract: Ticks are an important but under recognized parasitic threat to cats in many areas of the United States. To characterize the species and stages of ticks most commonly recovered from cats and determine the prevalence of disease agents in the ticks, we conducted a survey of ticks removed from cats at veterinary practices in 18 states from April 2016-June 2017. A total of 796 ticks were submitted from 332 cats from 41 different veterinary practices. A single tick was submitted from the majority of cats, with a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
67
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(78 citation statements)
references
References 36 publications
9
67
0
Order By: Relevance
“…Year-round ea and tick treatment coverage for cats directly protects the cat, eradicates ea populations in the home environment, 13 and helps to reduce the risk of vector transmitted disease. 1 However, as seen in this study, cat owners typically acquired only one or two treatment doses, regardless of the duration of the ea and tick medication purchased and few owners obtained full-year ea and tick coverage (Table 4). Therefore, veterinary clinicians and practice staff may want to pay increased attention to owner education and use of repurchase reminders as additional components that contribute to increased owner adherence.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Year-round ea and tick treatment coverage for cats directly protects the cat, eradicates ea populations in the home environment, 13 and helps to reduce the risk of vector transmitted disease. 1 However, as seen in this study, cat owners typically acquired only one or two treatment doses, regardless of the duration of the ea and tick medication purchased and few owners obtained full-year ea and tick coverage (Table 4). Therefore, veterinary clinicians and practice staff may want to pay increased attention to owner education and use of repurchase reminders as additional components that contribute to increased owner adherence.…”
Section: Discussionmentioning
confidence: 75%
“…This is because of the high prevalence of ea infestation, the year-round risk of ticks, the risk of ea allergy dermatitis (FAD), the pathogens that eas and ticks vector, and the introduction of eas into the home. 1,2 Fleas, particularly Ctenocephalides felis felis, are very common and perhaps the most clinically important ectoparasite of cats and dogs worldwide. [3][4][5] Flea-related diseases could account for more than half of dermatologic cases presented to companion animal veterinarians.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In primary care veterinary practice, ea and tick control is an essential component of the preventive healthcare strategy for cats. This is because of the high prevalence of ea infestation, the year-round risk of ticks, the risk of ea allergy dermatitis (FAD), the pathogens that eas and ticks vector, and the introduction of eas into the home [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Fleas and ticks also carry and transmit an assortment of vector-borne pathogens that can infect cats and people, including Bartonella spp., Ehrlichia spp., Rickettsia spp., Mycoplasma spp., as well as cestode, protozoal, and larial endoparasites [1,2,4,13,14]. Investigators have found that as many as 80% of eas collected from cat populations harbor feline or human pathogens of importance [15].…”
Section: Introductionmentioning
confidence: 99%